Purple passion fruit seeds (Passiflora edulis f. edulis Sims) as a promising source of skin anti-aging agents: Enzymatic, antioxidant and multi-level computational studies (2021)
ABSTRACT: This study aimed to assess the anti-aging potential of the ethanol extract of Passiflora edulis f. edulis Sims seeds, through in vitro determination of antioxidant activity and inhibition assays of some enzymes related to skin aging. Furthermore, using in silico methods (docking and molecular dynamics), were established the affinity of the majority compounds of the extract on the target enzymes, ending with the prediction of drug-likeness properties. The extract showed a high total phenolic content, represented mainly by flavonoids and phenolic acids, as well as a considerable antioxidant potential measured through the DPPH, FRAP and ORAC methods. In the inhibition assays of the enzymes collagenase, elastase and tyrosinase, IC50 values presented were optimal. Docking studies demonstrated marked binding ability of the extract constituients (specially, fisetin, galangin and S-eriodictyol) to the Collagenase and Tyrosinase. Molecular dynamics validated the stability and rationality of these molecular docking studies, MM/PBSA calculations provide strong evidence for both their specific heavy binding and how enzyme-ligand complex stabilized inside the catalytic domain, and drug-likeness studies showed suitable dermatopharmacokinetics indices for most of components of extract. Findings from this study suggest that ethanol extract of P. edulis has a great potential as an anti-aging agent.